Designing Nanoporous Coral‐Like Pt Nanowires Architecture for Methanol and Ammonia Oxidation Reactions. (14th December 2021) - Liu, Jie; Liu, Zhi; Wang, Haozhi; Liu, Bin; Zhao, Naiqin; Zhong, Cheng; Hu, Wenbin
Abstract: Improving Pt catalytic activity and minimizing its usage as well as enhancing its stability is highly desirable for oxidation of methanol and ammonia in the field of electrocatalysis. Herein, the nanoporous Pt with coral‐like nanowires morphology/carbon fiber cloth electrocatalyst is reported, which is synthesized via a simple electrodeposition approach using phytantriol lyotropic liquid crystals as template. The obtained electrode with 3D coral‐like Pt nanowires architecture is composed of the orderly in situ grown Pt nanowires, and each individual Pt nanowire possesses a large number of nanopores. As expected, coral‐like Pt nanowires electrodes possess high electrochemical surface area of 43.1 m 2 g ‐1, almost twice that (25.4 m 2 g ‐1 ) of commercial Pt/C, and thus display superior catalytic activity of 343.1 mA mg ‐1 and 72.0 mA mg ‐1 toward methanol and ammonia oxidation, much higher than that of the commercial Pt/C (173.7 mA mg ‐1 and 26.2 mA mg ‐1 ), respectively. Additionally, the retention rates of oxidation peak current of coral‐like Pt nanowires electrode toward both methanol and ammonia oxidation after accelerated 100 cycles test achieve 82.1% and 85.6%, respectively, indicating the excellent stability of coral‐like Pt nanowires electrode. Abstract : The obtained 3D coral‐like Pt nanowires, of which individual Pt nanowire possesses a porous structure, could maximize the potential of 1D Pt nanowires in electrocatalysis. This catalyst exhibits superior mass activity and cycling stability towards methanol and ammonia oxidation reaction.